کرپٹو کرنسی کاروبار کے متعلق فتاویٰ جات کا تحقیقی و تقابلی جائزہ: An Analytical and Comparative Study of Fatwas Regarding Crypto Currency Trade - Hafiz Muhammad Bashir Haideri (International Research Journal of Arabic and Islamic Studies, 2025)
Islam provides comprehensive guidance on all aspects of life, particularly on commercial transactions, with clear Islamic laws. As new trade methods emerge in every era, Islamic scholars issue fatwas considering Shariah’s principles. In the present era, crypto currency is gaining immense popularity worldwide, especially among the youth. Crypto currency is a digital currency created through a specific process and traded on various exchanges. Notably, it lacks physical existence and legal recognition in most countries. The majority of Islamic scholars consider crypto currency haram due to its inherent evils. However, some modern scholars and researchers deem it permissible, drawing analogies with electricity and gas. Conversely, others adopt a neutral stance, refraining from declaring it either Halal or Haram. This research aims to provide a comparative analysis of Fatwas from both perspectives, elucidating the arguments and rationale behind each stance. By doing so, this study seeks to provide clarity for individuals involved in crypto currency business, delineating the extent to which investing in crypto is Shariah-compliant.